Quantitative research on general practitioner policies in China from 1997 to 2023 - MA Xinru; ZHOU Yanxin; YAN Mengyu; LI Jing; SONG Shujie; SUN Mei (Shanghai yufang yixue)
ObjectiveTo understand the development stages and use of policy tools of general practitioner policies in China since it was first proposed, to summarize the experience and explore the shortcomings, so as to provide references for the adjustment and optimization of China’s general practitioner policies.MethodsContent analysis and mathematical statistics analysis were used to conduct a quantitative research on 111 policy documents with 422 policy items involving general practitioners at the national level from 1997 to 2023, through a three-dimensional analysis framework integrating policy tools, human capital process and policy development stages.ResultsCapacity‑building policy tools were most frequently used in general practitioner policies, and the policy tools gradually shifted from mandate to inducement. The general practitioner policies paid less attention to the career selection link, but paid full attention to every segment of human capital links, with a comprehensive application of policy tools observed in the integrated development stage, despite the existence of unbalanced internal distribution.ConclusionIt is suggested to promote the use of incentive policy tools and to explore multiple approaches based on incentive theory; pay attention to the career selection link for guiding the employment of general practitioners; take the appropriateness between the policy tools and human capital process into comprehensive consideration, striking a dynamic balance of the internal structure of general practitioner policies.